Yona of the dawn. 5 - Kusanagi, Mizuho, 1979-; MacFarlane, Ysabet Reinhardt (VIZ Media, 2017)
Princess Yona lives an ideal life as the only princess of her kingdom. Doted on by her father, the king, and protected by her faithful guard Hak, she cherishes the time spent with the man she loves, Su-Won. But everything changes on her 16th birthday when tragedy strikes her family. An earthquake suddenly hits the Village of the Blue Dragon, and Yona and her friends are trapped. Will Yona manage to escape safely? And will the Blue Dragon join her on her journey? Meanwhile, Gija senses the presence of the Green Dragon.